Export growth of NAFTA members, intra–industry trade and adjustment. (4th August 2014) - Brulhart, Marius; Thorpe, Michael
This paper looks at the issue of labour market adjustment in the context of expanded international trade of NAFTA economies both within the region and more generally. The study focuses on the period 1990–1998, a time frame that covers several years prior to and after the formation of NAFTA. Trade flows of the member countries are analysed using measures of static intra–industry trade (IIT) and dynamic (marginal) intra–industry trade (MIIT). Inferences are drawn from these results on the basis of the "smooth adjustment hypothesis" according to which IIT entails relatively low factor–market adjustment costs. The paper concludes that for trade flows within NAFTA, less labour market adjustment pressures are being experienced by the US and Mexico in terms of their relationship. A similar observation can be made for US–Canada trade. Trade between Canada and Mexico is seen as causing relatively more adjustment pressure compared to other intra–regional flows. In terms of the trade of NAFTA members with major trading partners outside of the group, the results are mixed.